The Magdalena, river of tombs and blessed souls: the persistence of memories - Herrera, Martha Cecilia; Torres Carrillo, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article presents a reflection on the imaginaries and symbolism present in some artistic creations (literature, visualand film) about the recent violence in Colombia, in which the Magdalena River has been a protagonist and in which can be seen the persistence of memories in the beliefs and representations of the riverside populations. Four aesthetic productions are analyzed that emphasize the river and the presence therein of spiritual and mythological beings in the discussed narrative corpus in order to recognise the metaphors and symbolismpresent in the literary and audiovisual narratives regarding political violence. This makes it possible to make an interpretive account with reference to the conceptual perspective of symbolic imagination.